Evolution of sugars and organic acid content in three pomegranate cultivars (Punica granatum L.) - Legua P.; Melgarejo P.; Martínez M.; Hernández F. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
The aim of the present work has been to study evolution of sugars and organic acids during development and ripening of pomegranate. The fruits analysed belong to the cultivars: ME5, ME17 and MO6. The investigation was carried out in 1997. Fruits were previously labelled in the same phenological stage and in the four tree orientations. Then they were analysed by HPLC fortnightly. pH and soluble solid changes were also tested. As a result of the study we can conclude that the predominant sugars are fructose and glucose with predominance of the latter. Saccharose and maltose contents are practically negligible. In relation to organic acids, malic acid is present in greater quantity than citric acid in some cultivars and vice versa in others. pH stabilises early in the development of the pomegranate. When approaching the ripening period a positive increase in the amount of soluble solids can be observed.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)